Pengaruh Kebijakan Dividen, Keputusan Pendanaan, dan Kualitas Laba terhadap Nilai Perusahaan - Kurniawan, Ginta Widya; Sunarto, Sunarto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to examine the effect of dividend policy, funding decisions, and earnings quality on firm value. This study uses the dependent variable of firm value and the independent variables of dividend policy, funding decisions, and earnings quality. The population in this study are non cyclical consumer sector companies listed on the Indonesia Stock Exchange peride 2018-2022. The total population or companies in the non-cyclical consumer sector is 113 companies. From this population, purposive sampling technique is used with several criteria to determine a sample of 12 companies. The data analysis technique in this study uses eviews 9 which includes descriptive statistical tests, panel data model analysis, classical assumption tests and hypothesis testing. Based on the test results, it proves that dividend policy, funding decisions, and earnings quality simultaneously affect firm value. Partially, dividend policy affects firm value, funding decisions have no effect on firm value, earnings quality has no effect on firm value.